Towards an Understanding of the Effects of Alteration on the Physical Properties of Mafic and Ultramafic Rocks. Issue 1 (1st December 2016) - Adams, Cameron; Dentith, Michael
Abstract : New physical rock property data from the Plutonic Well Greenstone Belt are presented. P-wave velocity (Vp), magnetic susceptibility and density measurements have been taken from rare stratigraphically complete drill core. Preliminary results show that variations of physical rock property data are successful in resolving most lithologies. However, questions remain regarding the interpretation of physical property data involving ultramafic and mafic rock, and, in particular, the effect of alteration. Variable alteration is suggested to be the cause of the wide ranges within physical property data populations. This problem is not exclusive to the Plutonic Well Greenstone Belt, and is a common feature within many greenstone terranes. Geochemical and mineralogical data are also available from the study area and may allow a better understanding of the effects of common types of alteration (serpentinisation, talc-carbonate alteration) on the physical properties of mafic and ultramafic rocks from granitoid-greenstone terrains.